Utilization of Web 2.0 Tools for Learning - T. Buan, Amelia (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This paper presents the results of a survey that investigated the degree of access and level of comfort on the use of Web 2.0 tools for learning. Students were asked to describe their experiences on the use of these tools and their responses were content analyzed. Familiar tools utilized by students were wikis, blogs,media sharing, online collaborative documents and social networking sites. Survey results show that students found Web 2.0 comfortable to use for research, as well as with peers and teachers. They express that these tools facilitate online collaboration, support social interaction, provide easy access to information, encourage self-direction, and promote critical thinking and communication skills. The paper recommends that educators utilize these tools in teaching to improve the learning process. Schools also need to provide an environment to support teachers and students in accessing web tools.